1993
DOI: 10.2331/suisan.59.487
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between Seawater Adaptability and Body Weight in 0+ Landlocked Rainbow Trout.

Abstract: A seawater challenge test was conducted on 0+ age-group landlocked rainbow trout On corhynchus mykiss to estimate the sufficient size for seawater culture. The seawater adaptability of fish of different body weights (averages respectively 50, 100, 150, and 200g) was assessed accoring to mortality, muscle moisture content, gill Na+-K+ATPase activity, and serum Na con centration, at intervals of 0, 6, 12, 24, 48, and 96h after direct transfer into seawater (31.6%). A high mortality occurred among fish in the 50g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
1

Year Published

1996
1996
2020
2020

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 0 publications
0
5
1
Order By: Relevance
“…The rainbow trout in a 200 g size class maintained significantly higher levels of muscle moisture content after the transfer to seawater than did the other smaller size classes (Gorie, 1993). Again, in comparison to the previous studies on rainbow trout reported by Leray et al (1981) and Gorie (1993), steelhead trout in the current study seem to be able to maintain muscle moisture better than landlocked rainbow trout of the similar size.…”
Section: Muscle Moisture Contentscontrasting
confidence: 54%
See 4 more Smart Citations
“…The rainbow trout in a 200 g size class maintained significantly higher levels of muscle moisture content after the transfer to seawater than did the other smaller size classes (Gorie, 1993). Again, in comparison to the previous studies on rainbow trout reported by Leray et al (1981) and Gorie (1993), steelhead trout in the current study seem to be able to maintain muscle moisture better than landlocked rainbow trout of the similar size.…”
Section: Muscle Moisture Contentscontrasting
confidence: 54%
“…No mortality was observed in the 100 g weight group, while mortality in both the 50 and 150 g weight groups was 2.6% ( Table 1 ). In a previous study of a landlocked O. mykiss strain, Gorie (1993) reported a 29% mortality in the 50 g size class compared to 3% and 6% mortality in 100 and 150 g size classes, respectively, 96 h after seawater transfer. In comparison with the previous study by Gorie (1993) , under our experimental conditions the current mortality results after seawater transfer indicate that steelhead trout has a higher tolerance to seawater (32 ppt) than landlocked O. mykiss of the same size.…”
Section: Resultsmentioning
confidence: 86%
See 3 more Smart Citations